2022
DOI: 10.3389/fphar.2021.768015
|View full text |Cite
|
Sign up to set email alerts
|

Investigating Toxin Diversity and Abundance in Snake Venom Proteomes

Abstract: Understanding snake venom proteomes is becoming increasingly important to understand snake venom biology, evolution and especially clinical effects of venoms and approaches to antivenom development. To explore the current state of snake venom proteomics and transcriptomics we investigated venom proteomic methods, associations between methodological and biological variability and the diversity and abundance of protein families. We reviewed available studies on snake venom proteomes from September 2017 to April … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
45
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 46 publications
(48 citation statements)
references
References 59 publications
(88 reference statements)
3
45
0
Order By: Relevance
“…Globally, elapid venoms have been shown to mostly be composed of low-molecular-weight toxins belonging to the protein families 3FTx and/or PLA 2 . Combined, these two dominant toxin families typically make up almost 80% of elapid venoms [ 19 , 20 ]. In contrast, we show that almost half of the venom of H. stephensii is made up of high-molecular-weight proteins—SVMP (36.7%) and LAAO (10.8%).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Globally, elapid venoms have been shown to mostly be composed of low-molecular-weight toxins belonging to the protein families 3FTx and/or PLA 2 . Combined, these two dominant toxin families typically make up almost 80% of elapid venoms [ 19 , 20 ]. In contrast, we show that almost half of the venom of H. stephensii is made up of high-molecular-weight proteins—SVMP (36.7%) and LAAO (10.8%).…”
Section: Discussionmentioning
confidence: 99%
“…Although approximately 50 different protein families have been identified in snake venoms worldwide, most snake venoms have been shown to be largely composed of four dominant protein families; three-finger toxins (3FTx), phospholipase A 2 (PLA 2 ), snake venom metalloprotease (SVMP), snake venom serine protease (SVSP), and six secondary protein families; L-amino acid oxidase (LAAO), kunitz peptides (KUN), cysteine-rich secretory proteins (CRiSP), natriuretic peptides (NP), C-type lectins (CTL), and disintegrins (DIS) [ 19 , 20 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite such a big diversity, the number of protein or peptide structural families represented in animal venoms is not very large. For example, about two dozen families can be found in snake venoms [ 9 ]. The most abundant families of snake toxins are phospholipases A2 (PLA2), three-finger toxins (3FTx), snake venom serine proteases (SVSP), and snake venom metalloprotease (SVMP).…”
Section: Animal Venom and Their Componentsmentioning
confidence: 99%
“…In addition, the proteomic analysis unveiled the richness of pharmacologically active molecules in the species’ venom, suggesting its potential for drug discovery. The second in-depth review article, by Tasoulis et al (2022) , explored the current state of venom proteomic methods, associations between methodological and biological variability and the diversity and abundance of protein families, reported for snake venom proteomes from September 2017 to April 2021. The review included a total of 81 venom proteomic studies of 79 snake species, where relative toxin abundance was reported for 70 species and toxin diversity (number of different toxins) was reported for 37 species.…”
mentioning
confidence: 99%